A supersymmetric theory of baryogenesis and sterile sneutrino dark matter from B mesons - Alonso Álvarez, Gonzalo; Elor, Gilly; Nelson, Ann E.; Xiao, Huangyu (Journal of high energy physics, 2020)
Low-scale baryogenesis and dark matter generation can occur via the production of neutral B mesons at MeV temperatures in the early Universe, which undergo CP-violating oscillations and subsequently decay into a dark sector. In this work, we discuss the consequences of realizing this mechanism in a supersymmetric model with an unbroken U(1)R symmetry which is identified with baryon number. B mesons decay into a dark sector through a baryon number conserving operator mediated by TeV scale squarks and a GeV scale Dirac bino. The dark sector particles can be identified with sterile neutrinos and their superpartners in a type-I seesaw framework for neutrino masses. The sterile sneutrinos are sufficiently long lived and constitute the dark matter. The produced matter-antimatter asymmetry is directly related to observables measurable at B factories and hadron colliders, the most relevant of which are the semileptonic-leptonic asymmetries in neutral B meson systems and the inclusive branching fraction of B mesons into hadrons and missing energy. We discuss model independent constraints on these experimental observables before quoting predictions made in the supersymmetric context. Constraints from astrophysics, neutrino physics and flavor observables are studied, as are potential LHC signals with a focus on novel long lived particle searches which are directly linked to properties of the dark sector.
Gesehen am 21.04.2020